Removal of Methylene Blue from Wastewater Using AL Haji Plant as a Low-Cost, Eco-Friendly Adsorbent - Adday, Ruqaya; Flayeh, Hussein (Al-Khwarizmi Engineering Journal, 2025)
This study investigates the use of agricultural waste, specifically the Al Haji plant, for wastewater treatment. The term 'Al Haji plant' refers to species from the Al Haji genus, particularly "Al Haji maurorum " and "Al Haji canescens ", which are drought-resistant plants of the Fabaceae family. Traditionally, these plants are known for their medicinal and antimicrobial properties. In this research, waste from the Al Haji plant was converted into activated carbon (AC) as a low-cost and techno-economically viable biosorbent for the removal of methylene blue (MB) dye from wastewater. The production of AC involved two key steps: chemical activation using sodium hydroxide (NaOH) and carbonisation at 300 °C. The properties and adsorption potential of the resulting AC were investigated. Various parameters were studied, including pH, contact time, stirring rate, initial dye concentration, adsorbent dosage, and temperature. Characterisation of the biosorbents was performed using Scanning Electron Microscopy (SEM) and Brunauer–Emmett–Teller (BET) surface area analysis. The SEM investigation showed notable pores in the Al Haji plant sample that could enhance the absorption of the MB dye. Results indicated that the BET surface area for physical AC is 25.5796 m²/g. The surface area of chemical AC was reported as 16.2767 m²/g. The dye exhibited pseudofirst-order adsorption kinetics, with average rate constants of 0.020082 and 0.001589 for physical and chemical activation approaches, respectively. An adsorption isotherm study was performed using the Langmuir model, which showed an R² value of 0.827 and a maximum adsorption capacity of 5.24 mg/g." The study of adsorption thermodynamics revealed that MB adsorption on Al Haji activated carbon is spontaneous and endothermic.